The Role of National Culture in the Spiritual Education of Youth - Sagdullayeva F. B (International Journal on Integrated Education, 2022)
This article analyzes the role of national culture in the education of the spiritual appearance of youth, in the formation of the younger generation of feelings of patriotism, humanism and tolerance.